Validation of a Leadership Self-Efficacy Scale for Educational Leaders - Tan, Rhigel; Alderite, Thelma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to validate a scale that evaluates the leadership self-efficacy among educational leaders. The 92-item scale was developed by group of educational leadership practitioners at a Philippine university headed by Dr. Tan (2025) and was approved for use. To do so, the scale was administered to 200 educational leaders holding different positions. The data obtained were subjected to Exploratory Factor Analysis (EFA) and created a seven-factor model. The factors are set of leadership skills named as Continuous Learning and Professional Growth (Factor 1), Stress Management and Well-being (Factor 2), Communication and Collaboration (Factor 3), Inspirational and Visionary Leadership (Factor 4), Integrity and Ethical Leadership (Factor 5), Adaptability and Resilience (Factor 6), and Mentorship and Empowerment (Factor 7). The model was confirmed utilizing the resulting values of five goodness of fit indices (GFIs) generated by the Confirmatory Factor Analysis (CFA). All GFIs resulted to values falling within the thresholds. These GFIs are already adequate to confirm that the model is relatively good fit. The standardized factor loadings (SFLs) and composite reliability (CR) were also excellent, thus, establishing convergent validity. Also, the estimated average variance extracted of all factors provided evidence of discriminant validity and reliability, respectively. Overall, the study resulted in a valid and reliable 26-item scale that effectively measures leadership self-efficacy among educational leaders.